PENGARUH DEWAN KOMISARIS INDEPENDEN, KOMITE AUDIT, KUALITAS AUDIT, KEPEMILIKAN MANAJERIAL DAN DIVIDEND PAYOUT RATIO TERHADAP PERATAAN LABA - Rahmini, Restu; Panggabean, Rosinta Ria (Ultimaccounting Jurnal Ilmu Akuntansi, 2019)
Abstract The purpose of this study is to analyse the influence of the Independent Board of Commissioners, Audit Committee, Audit Quality, Managerial Ownership and Dividend Payout Ratio on income smoothing and company size as a control variable. The sample in this study are Property and Real Estate sector companies listed on the Indonesia Stock Exchange (BEI) and Bursa Malaysia (KLSE) in 2014-2017. This study used purposive sampling method, logistic regression analysis, and classic assumption test. Income smoothing can be measured using dummy variables. The results of the analysis show that the variables that affect income smoothing on the Bursa Malaysia are managerial ownership and control variables, namely the size of the companies listed, while the Independent Board of Commissioners, Audit Committee, Audit Quality, managerial ownership, Dividend Payout Ratio and company size have no effect on income smoothing on the Indonesia Stock Exchange securities.